2015
DOI: 10.1038/srep09284
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Patatin-Like Phospholipase Domain Containing 3 Gene (PNPLA3) Polymorphisms and Nonalcoholic Fatty Liver Disease: A HuGE Review and Meta-Analysis

Abstract: We conducted a meta-analysis to assess the association between patatin-like phospholipase domain-containing 3 (PNPLA3) rs738409 polymorphism and nonalcoholic fatty liver disease (NAFLD) and its subtypes simple steatosis(SS) and nonalcoholic steatohepatitis (NASH). The study-specific odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using fixed-effects or random-effects models, with assessment for heterogeneity and publication bias. Twenty-three case-control studies involving 6071 NAFLD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 47 publications
(156 reference statements)
9
84
0
3
Order By: Relevance
“…This is in accordance with the results of many trials which showed an association between the rs738409 polymorphism and the risk of NAFLD [32]- [34]. The exact mechanisms by which the I148M polymorphism increases the susceptibility to NAFLD and its influence on the histological severity of NAFLD still remains to be fully elucidated [35]. The homozygous GG genotype was most frequent among the patients with NASH (26%) when compared to subjects with borderline NASH (20.5%) and those with simple steatosis (20%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with the results of many trials which showed an association between the rs738409 polymorphism and the risk of NAFLD [32]- [34]. The exact mechanisms by which the I148M polymorphism increases the susceptibility to NAFLD and its influence on the histological severity of NAFLD still remains to be fully elucidated [35]. The homozygous GG genotype was most frequent among the patients with NASH (26%) when compared to subjects with borderline NASH (20.5%) and those with simple steatosis (20%).…”
Section: Discussionsupporting
confidence: 90%
“…This was concordant to the results of the meta-analysis by Sookoian and Pirola which showed that the rs738409 exerts a strong influence on the susceptibility to a more aggressive disease with greater hepatic injury, as the GG homozygous subjects had a 3.24-fold more risk of higher necro-inflammatory scores when compared with those who had the CC genotype [8]. Also a meta-analysis by Xu et al reported that the rs738409 polymorphism was more likely to increase the risk of NASH instead of simple steatosis [35]. Zain and Mohamed, demonstrated a significant association between the GG genotype and the fibrosis stage (p = 0.038); patients with GG genotype had a greater mean score of 2.03 compared to those with the CC genotype who had a mean score of 1.52.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported similar results and further highlighted the fact that rs738409 [G] was not merely associated with steatosis but also with severe liver damage throughout the NAFLD spectrum [12][13][14]. These findings have been summarized in several meta-analyses [15][16][17][18][19] (Table 1). Since the physiopathology of NAFLD is tightly related to the metabolic syndrome, a link between rs738409[G] and the parameters that define the metabolic syndrome was a likely hypothesis.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 52%
“…The disease has two very distinct clinical presentations: the primary form or diet-induced NAFLD and secondary forms, which occur in patients with various apparently unrelated diseases [2]. It is known that NAFLD and alcoholic fatty liver disease (AFLD) share similar histopathological and molecular biological features, as well as identical polymorphism in the patatin-like phospholipase domain-containing 3 gene (PNPLA3) [3][4][5]. Besides, the finding that patients with nonalcoholic steatohepatitis (NASH) produce more endogenous ethanol (EE) than control subjects further strengthens this connection [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%